Optimizing the use of Domestic Products Within the Ministry of State Apparatus and Bureaucratic Reforms - Andre Rosi Pradita; Asropi; Neneng Sri Rahayu (Universitas Muhammadiyah Palu, 2025)
The use of domestic products is a form of commitment to the government's role in supporting and ensuring national economic independence and stability. By using domestic products, it is expected to be able to restore the role of the national economy. One of the efforts made by the government in increasing domestic products by issuing several regulations, such as Law Number 3 of 2014 concerning Industry which encourages the use of domestic products, even in 2022 the government issued INPRES Number 2 of 2022 concerning Accelerating the Use of Domestic Products. Based on these regulations, it emphasizes that the central government and local governments should increase the use of domestic products. This research was conducted at the Ministry of PANRB by looking at three variables in the implementation of the use of domestic products including policy, organization, and environment. This research uses qualitative methods by conducting in-depth interviews, observations, and by using documents to obtain information and data. Although there are still some employees who think that the quality of domestic products is lower than foreign products. In its application, the head of the organization plays a key role in the use of domestic products.